Tax Compliance of MSMEs in Makassar: Digitalization and Tax Literacy with Trust as a Moderating Variable - Muh. Arsyad; Asriani Junaid; Ratna Sari; Hasanuddin (Jurnal Riset Perpajakan: Amnesty, 2026)
Tax compliance is a crucial factor in optimizing state revenue, particularly from the Micro, Small, and Medium Enterprises (MSMEs) sector, which significantly contributes to the national economy. In the digital era, the government continues to promote tax administration transformation through various technology-based services to improve the ease and effectiveness of fulfilling tax obligations. However, MSMEs still face various challenges related to tax understanding and trust in tax authorities. This study aims to analyze the impact of tax digitalization and tax literacy on MSME tax compliance in Makassar City and examine the role of trust as a moderating variable. The study employed a quantitative approach with a survey method. The study population comprised small businesses (MSMEs) in Makassar City. A sample of 100 respondents was determined using the Slovin formula with a 10% error rate. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of the SmartPLS application. The results of the study indicate that tax digitalization has a positive and significant impact on MSME tax compliance. Tax literacy was also shown to have a positive and significant impact on tax compliance. However, trust did not moderate the relationship between tax digitalization and tax compliance, nor did it moderate the relationship between tax literacy and tax compliance. These findings suggest that MSME tax compliance is more influenced by the ease of the digital tax system and the level of tax understanding than by trust. This study provides implications for tax authorities to continuously improve the quality of digital services and tax education programs to strengthen MSME tax compliance sustainably.